HUBUNGAN GREEN PRODUCT, GREEN ROOM LAYOUT, DAN SERVICE QUALITY TERHADAP REPURCHASE INTENTION PADA PEMBELAJARAN MAHASISWA KAMPUS X - Budi Christanto; Christy Ayu Sarah Panjaitan; Abigail Theodora Tanzil; Christian Gregory (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Growing environmental awareness has encouraged higher education institutions to integrate sustainability principles into learning activities. The implementation of environmentally friendly concepts on campus, such as green products, green room layout, and improved service quality, is believed to influence students’ learning experiences and foster their loyalty to educational institutions. This study aims to analyze the effects of green product, green room layout, and service quality on students’ repurchase intention in the learning context at Campus X. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 176 students selected using purposive sampling, with the sample size determined using the Slovin formula. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that green product has a positive and significant correlation on students’ repurchase intention. Furthermore, green room layout also shows a positive and significant correlation on repurchase intention. Service quality emerges as the most dominant variable, exerting a strong and significant correlation on repurchase intention compared to the other variables. Simultaneously, green product, green room layout, and service quality explain 63.2% of the variance in students’ repurchase intention. These findings highlight that the implementation of an integrated green campus concept supported by high-quality educational services can create sustainable learning experiences, enhance student loyalty, and promote environmental awareness within higher education institutions. ABSTRAK Peningkatan kesadaran terhadap isu lingkungan mendorong perguruan tinggi untuk mengintegrasikan prinsip keberlanjutan dalam kegiatan pembelajaran. Penerapan konsep ramah lingkungan di lingkungan kampus, seperti penggunaan green product, green room layout, dan peningkatan service quality, diyakini dapat memengaruhi pengalaman belajar mahasiswa serta mendorong loyalitas mereka terhadap institusi pendidikan. Penelitian ini bertujuan untuk menganalisis pengaruh green product, green room layout, dan service quality terhadap repurchase intention mahasiswa pada pembelajaran di Kampus X. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Data dikumpulkan melalui penyebaran kuesioner kepada 176 mahasiswa yang dipilih menggunakan teknik purposive sampling, dengan jumlah sampel ditentukan berdasarkan rumus Slovin. Analisis data dilakukan menggunakan Partial Least Squares–Structural Equation Modeling (PLS-SEM) dengan bantuan SmartPLS 4. Hasil penelitian menunjukkan bahwa green product berhubungan positif dan signifikan terhadap repurchase intention mahasiswa. Selain itu, green room layout juga terbukti memiliki hubungan positif dan signifikan terhadap repurchase intention. Variabel service quality menunjukkan hubungan paling dominan dan signifikan terhadap repurchase intention dibandingkan variabel lainnya. Secara simultan, ketiga variabel tersebut mampu menjelaskan 63,2% variasi repurchase intention mahasiswa. Temuan ini menegaskan bahwa penerapan konsep green campus yang terintegrasi dengan kualitas layanan pendidikan yang baik dapat menciptakan pengalaman belajar yang berkelanjutan, meningkatkan loyalitas mahasiswa, serta menumbuhkan budaya kepedulian lingkungan di lingkungan perguruan tinggi.